INNOVATIVE PRODUCT STARTUP BUSINESS MODEL - B. Tokarev (Вестник университета, 2018)
The business models modern concepts have been analyzed. The comparative study of startups business models conduct. The analysis of business models study for several options. Features of their application are studied, as well as their strengths and weaknesses. It is shown variants of business models realization for a new product and for innovative. The features in application to startups of innovative products models are dened. The specic properties of startup innovations that require multiple product redevelopment and search for strategy progress are revealed. The author’s model of innovative products startup containing a feedback loop is oered.